Preface: Special issue on the Twelfth International Symposium on Networking and Computing - Nakano, Koji (International Journal of Networking and Computing, 2025)
The Twelfth International Symposium on Computing and Networking (CANDAR 2024) was held from November 26 to 29, 2024, in Naha, Okinawa, Japan. Following the symposium, authors of highly evaluated papers were invited to submit extended versions for consideration in this special issue. After a rigorous peer-review process, nine papers were accepted and are published here as extended versions.We would like to express our sincere gratitude to the anonymous reviewers who carefully evaluated the submissions and provided insightful comments and suggestions. Their dedicated efforts and constructive feedback were instrumental in enhancing the quality of the accepted papers and shaping the content of this issue.Finally, we extend our heartfelt thanks to all those who contributed to the success of this special issue--including the organizers, guest editors, and reviewers. Their collective contributions made it possible to present this collection of extended papers, which reflect recent advances in networking and computing. We hope this issue will serve as a valuable resource for researchers and practitioners and inspire further innovation in the field.